Familial Hypercholesterolaemia: An Updated Overall Management - Mohd Kasim, Noor Alicezah; An, Chua Yung; Nawawi, Hapizah (2020)
Familial hypercholesterolaemia (FH), the commonest and serious but potentially treatable form of inherited dyslipidaemias, is characterised by severely elevated plasma low-density lipoprotein-cholesterol (LDL-C) level, which subsequently leads to premature coronary artery disease (pCAD). Effectiveness of FH early detection and treatment is supported by the outcome of several international cohort studies. Optimal FH management relies on prescription of statins either alone or together with other lipid-lowering therapies (LLT). Intensive lifestyle intervention is required in parallel with LLT, which should be commenced at diagnosis in adults and childhood. Treatment with high intensity statin should be started as soon as possible. Combination with ezetimibe and/or bile acid sequestrants is indicated if target LDL-C is not achieved. For FH patients in the very-high risk category, if their LDL-C targets are not achieved, despite being on maximally tolerated statin dose and ezetimibe, proprotein convertase subtilisin/kexin type1 inhibitor (PCSK9i) is recommended. In statin intolerance, ezetimibe alone, or in combination with PCSK9i may be considered. Clinical evaluation of response to treatment and safety are recommended to be done about 4-6 weeks following initiation of treatment. Homozygous FH (HoFH) patients should be treated with maximally tolerated intensive LLT and, when available, with lipoprotein apheresis. This review highlights the overall management, and optimal treatment combinations in FH in adults and children, newer LLT including PCSK9i, microsomal transfer protein inhibitor, allele-specific oligonucleotide to ApoB100 and PCSK9 mRNA. Family cascade screening and/or screening of high-risk individuals, is the most cost-effective way of identifying FH cases and initiating early and adequate LLT.